2017
DOI: 10.17159/sajs.2017/20170092
|View full text |Cite
|
Sign up to set email alerts
|

South Africa's geothermal energy hotspots inferred from subsurface temperature and geology

Abstract: ARTICLE INCLUDES: Supplementary material × Data set FUNDING:None South Africa intends to mitigate its carbon emissions by developing renewable energy from solar, wind and hydro, and investigating alternative energy sources such as natural gas and nuclear. Low-enthalpy geothermal energy is becoming increasingly popular around the world, largely as a result of technological advances that have enabled energy to be harnessed from relatively low temperature sources. However, geothermal energy does not form part of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…For our initial temperature, we use the average heat flow of the Namaqua-Natal basement of 61 ± 11 mW/m 2 (Jones, 1993) and solve for the steady state geothermal gradient considering the stratigraphic profile used in the calculation. The resulting geothermal gradient of about 25.3°C/km is consistent with Jones (1993) and Dhansay et al (2017).…”
Section: Model Initialization and Boundary Conditionssupporting
confidence: 88%
“…For our initial temperature, we use the average heat flow of the Namaqua-Natal basement of 61 ± 11 mW/m 2 (Jones, 1993) and solve for the steady state geothermal gradient considering the stratigraphic profile used in the calculation. The resulting geothermal gradient of about 25.3°C/km is consistent with Jones (1993) and Dhansay et al (2017).…”
Section: Model Initialization and Boundary Conditionssupporting
confidence: 88%
“…There is also reported soil liquefaction in Florisbad roughly 150 km northeast of Koffiefontein (e.g., Visser & Joubert, 1990). In a recent study, Dhansay et al (2017) shows moderate-to-high production of geothermal heat (refer to Figure 3 of this study) at surface or very shallow crustal depths Koffiefontein and its immediate surroundings. This suggests that there are some areas either with high heat flow but trapped by shallow crustal rocks or areas with hot springs which are trapped in the subsurface and have no hydrothermal plumbing to the surface.…”
Section: Journal Of Geophysical Research: Solid Earthmentioning
confidence: 51%
“…Because heat from the mantle cannot penetrate close enough to the surface; hence, drilling for geothermal sources greater than 5 km becomes a very expensive development (about R1.45 billion for only 50 MW geothermal power). 2 The low price and high availability of fossil fuels along with a lack of knowledge of the technology necessary to explore geothermal resources are some of the factors that limit South Africa's prospects for geothermal energy production.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the organic rankine cycle (ORC) technology could be implemented and used to generate high-pressure steam from very low-quality heat (using low temperature geothermal sources). 3,4 Dhansay et al 2 investigated South Africa's geothermal energy hotspots inferred from subsurface temperature and geology. The study identified five promising regions in South Africa where lowenthalpy geothermal energy can be explored and developed ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation